Effective parameters on second law analysis for semicircular ducts in laminar flow and constant wall heat flux - Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2005)
Entropy generation for semi-cylindrical ducts is obtained analytically for laminar flow and subjected to constant wall heat flux boundary conditions. Affecting parameters such as heat flux rate, Reynolds number and cross sectional are studied for entropy generation. It is concluded that cross-sectional area and wall heat flux have considerable effect on entropy generation. For the increasing value of these parameters, both entropy generation and pumping power ratio are increased at fixed Reynolds number. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: second law analysis; laminar flow; semi-circular duct